DMPP reduced nitrification, but not annual N2O emissions from mineral fertilizer applied to oilseed rape on a sandy loam soil. Issue 12 (5th September 2019) - Thers, Henrik; Petersen, Søren O.; Elsgaard, Lars
Abstract: Direct field emissions of nitrous oxide (N2 O) may determine whether biodiesel from oilseed rape ( Brassica napus L.) fulfills the EU requirement of at least 50% reduction of greenhouse gas emissions as compared to fossil diesel. However, only few studies have documented fertilizer N emission factors (EF) and mitigation options for N2 O emissions from oilseed rape cropping systems. We conducted a field experiment with three N levels (0, 171, and 217 kg/ha), where the N fertilizer was applied as ammonium sulfate nitrate with or without the nitrification inhibitor 3, 4‐dimethylpyrazole phosphate (DMPP). N2 O fluxes were measured using static chambers technique and soil samples were analyzed for water and mineral N content during a monitoring period of 368 days. The DMPP treatments showed a significantly increased level of ammonium ( NH 4 + ) for up to 18 weeks after spring fertilization as compared to the treatments without DMPP. However, this difference did not result in a corresponding decrease in NO 3 - soil content, and no differences in cumulative N2 O emissions were found between any fertilized treatments with or without DMPP (mean, 1.26 kg N2 O‐N ha −1  year −1 ). More field experiments are needed to clarify whether DMPP‐coated mineral fertilizers could mitigate N2 O emissions under different weather conditions, for example, under conditions where fertilization events concurred with rainfall events increasing water‐filled pore space to the assumed 60% threshold for denitrification. Emission factors for mineral N fertilizer were 0.28%–0.36% with a mean of 0.32% across the fertilized treatments. These data concur with recent European studies suggesting that the EF for mineral N fertilizers in oilseed rape cropping systems may typically be lower than the default IPCC value of 1%. Further studies are needed to consolidate an EF for oilseed rape under temperate conditions, which will be determining for the sustainability of Northern European oilseed rape cultivation for biodiesel. Abstract : The sustainability of oilseed rape‐based biodiesel is challenged by soil nitrous oxide (N2 O) emissions related to the cultivation step. However, uncertainty remains regarding the magnitude and potential mitigation of N2 O field emissions. This field experiment measured the N2 O emissions through 1 year while also testing a nitrification inhibitor (NI) as possible N2 O mitigation agent. We found the N2 O emissions to be lower than generally expected, but did not find an effect of the NI. This means that the general sustainability of oilseed rape‐based biodiesel is better than believed; however, no further reductions due to specific management actions could be confirmed.